Modification of the pierce instability of the electron flow in a diode with an external electromagnetic action - Melezhik, O.G.; Pashchenko, A.V.; Romanov, S.S.; Shapoval, I.M. (Вопросы атомной науки и техники, 2014)
The stability of electron fiow passage through the diode with a neutralized space charge has been investigated on the basis of the first-order approximation for hydrodynamic and Maxwell equations. Classification of solutions to the equations was developed in accordance with the magnitude and nature (potential or eddy) of the electric field arising at the diode cathode. The stability regions for these states have been found. It is shown that the presence of external electromagnetic action makes the stability region narrower than that predicted by Pierce. На основе решения системы гидродинамических уравнений и уравнений Максвелла в первом приближении изучена устойчивость прохождения электронного потока через диод с компенсированным объемным зарядом. Проведена классификация решений уравнений в соответствии с величиной и характером (потенциальное или вихревое) электрического поля, возникающего на катоде диода. Найдены области устойчивости этих состояний. Показано, что наличие внешнего электромагнитного воздействия сужает область устойчивости по сравнению с предсказанной Пирсом. На основi розв'язання системи перших наближень гiдродинамiчних рiвнянь та рiвнянь Максвела вивчена стiйкiсть проходження електронного потоку через дiод з компенсованим об'ємним зарядом. Проведена класифiкацiя рiшень рiвнянь у вiдповiдностi з величиною та характером (потенцiйне або вихрове) електричного поля, що виникає на катодi дiода. Найдено областi стiйкостi цих станiв. Показано, що наявнiсть зовнiшнього електромагнiтного впливу звужує область стiйкостi порiвняно з передбаченою Пiрсом.